Mosquito Nets as Predicting of Malaria Prevention in Endemic Areas - Susanto, Nugroho; Lanni, Fransiska; Pascawati, Nur Alvira (Media Kesehatan Masyarakat, 2024)
Endemic areas are risk factors for malaria transmission. The community who traveling to malaria endemic areas only 18.7% prepare malaria drugs. Behavior as a factor in reducing incidence of malaria. Eradicating malaria is very difficult to do because it is related behavior, environment and no vaccine as prevent malaria. The study objective to determine dominant factors of malaria prevention behavior in endemic areas. The study design with cross-sectional. The study population was students in at Respati University in. The sample size required was 78 samples. The independent variables include mosquito nets, repellents, mosquito coils, improved nutrition, and keeping fish. Dependent variable is endemic status. Data were analyzed with chi square and logistic regression. Majority of subjects no used mosquito nets 82.1%, no repellents 83.3%, no mosquito coils 79.5%, no nutritious 73.1%, no raise fish 75.6%. There were differences in the behavior of using mosquito nets between endemic and non-endemic areas p = 0.041, no differences used of repellents (p = 0.378), mosquito repellents (p = 0.519), no nutrition status (p = 0.842), and significant differences in raise fish (p = 0.003). Raising fish is more dominant factor contributing endemic areas (β = -2.12) compared mosquito nets (β = -1.530). The preventing for transmission of malaria based on the endemic area is mosquito nets and raising fish. The behavior of raise fish more dominant factor compared mosquito nets in endemic areas. Keywords: Malaria, endemic, prevention.